Op-amp Based Automatic Umbrella - Pramod Kumar; Prakash Dashore; Ravidra Pratap; Satyam Patel (International Journal of Advanced Robotics and Automation Technology, 2023)
The objective of the dissertation is to develop a smarter cover that, due to its practicality and accessibility, may lessen the need for human labour. In today's civilization, which is exposed to wind and rain without adequate safeguards, this is vital. The objective of this investigation is to develop a commercial, residential cover that is very sensitive to situations involving the sun and the rain. Operating on the surface of wide areas is challenging due to the extreme temperature of the sun, especially in the high seasons of summer.
Keywords: DC Motor; IR sensor; Processing App; Rain; folding canopy